Analisis Pemahaman Siswa Kelas Rendah Terhadap Konsep Perkalian pada Pembelajaran Tematik Terpadu di SD/MI - Arfani, Asyifa Luthfiana; Yuliawati, Fitri (AR-RIAYAH: Jurnal Pendidikan Dasar, 2021)
The background of this research is due to the lack of understanding of low-grade students regarding the concept of multiplication in thematic subjects. The purpose of this study was to determine the level of understanding of low grade students in understanding the concept of multiplication. This study uses a qualitative method, by examining data sources from several students. In addition, the researchers also conducted a literature study on several sources of books and articles to enrich the information. The sample in this study were 15 low-grade students. The instrument used is a test to measure the knowledge and abilities of students. The data obtained were then processed and analyzed using descriptive qualitative analysis techniques. The results showed that: (1) The average value of understanding 15 students about the basic concept of multiplication was 67.33%; (2) The lack of inculcation of the basic concept of multiplication counting operations is not carried out early on; (3) Students' skills in understanding the basic method of multiplication are still lacking; (4) The achievement and encouragement of students in learning on multiplication operations is still low.